Mitochondrial sirtuin 3 and various cell death modalities - Yapryntseva, Maria A.; Maximchik, Polina V.; Zhivotovsky, Boris; Gogvadze, Vladimir (Frontiers in Cell and Developmental Biology, 2022)
Sirtuin 3, a member of the mammalian sirtuin family of proteins, is involved in the regulation of multiple processes in cells. It is a major mitochondrial NAD+-dependent deacetylase with a broad range of functions, such as regulation of oxidative stress, reprogramming of tumor cell energy pathways, and metabolic homeostasis. One of the intriguing functions of sirtuin 3 is the regulation of mitochondrial outer membrane permeabilization, a key step in apoptosis initiation/progression. Moreover, sirtuin 3 is involved in the execution of various cell death modalities, which makes sirtuin 3 a possible regulator of crosstalk between them. This review is focused on the role of sirtuin 3 as a target for tumor cell elimination and how mitochondria and ROS are implicated in this process.